A revision of the Heatherellidae (Parasitiformes: Mesostigmata) with a new genus and two new species from Australasia - Seeman, Owen D.; Minor, Maria; Baker, Michelle R.; Walter, David Evans (Zootaxa, 2018)
The discovery of a new genus of Heatherellidae in New Zealand has led us to revise this enigmatic family and its constituent genera. Aheatherella n. gen., based on A. mira n. sp. from the North Island of New Zealand, lacks some of the derived character states that link the Australian Heatherella, most notably the lack of sexual dimorphism in the dorsal shields and in the presence of peritremes in adult Aheatherella. Heatherella osleri n. sp. is described from New South Wales, extending the distribution of this genus beyond Queensland. New collection records of H. callimaulos and a key to the genera and species of the family are provided. We propose that the Heatherellidae—previously placed in its own cohort outside the Gamasina—are best considered a superfamily of gamasine mites within the subcohort Epicriiae.